1997
DOI: 10.1002/(sici)1097-0215(19971127)73:5<639::aid-ijc5>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4, pRB, p53 and cyclin D1 expression and hypermethylation of CDKN2 gene in thymoma and thymic carcinoma

Abstract: There have been few reports on genetic alterations in thymomas. To investigate the expression of p16 INK4A , RB, p53 and cyclin D1 in thymomas, we first examined 36 thymomas (non-invasive type, 16 cases; invasive type, 20 cases) and 3 thymic carcinomas, using immunohistochemistry. Abnormal expression of p16 INK4A , RB, p53 and cyclin D1 was observed in 18, 8, 10 and 7 cases, respectively. Only a subgroup of invasive thymomas and thymic carcinomas showed an inverse correlation between p16 INK4A and RB expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 12 publications
2
39
0
Order By: Relevance
“…Correspondingly, previous reports have shown that inactivation of p16 INK4A , which results in higher CDK4 activity (35), is involved in the progression of TEMs (36). Regarding EGFR, which is frequently overexpressed in TEMs (23), mutations that alter its susceptibility towards different inhibitors are rare in this cancer (37)(38)(39).…”
Section: Discussionmentioning
confidence: 88%
“…Correspondingly, previous reports have shown that inactivation of p16 INK4A , which results in higher CDK4 activity (35), is involved in the progression of TEMs (36). Regarding EGFR, which is frequently overexpressed in TEMs (23), mutations that alter its susceptibility towards different inhibitors are rare in this cancer (37)(38)(39).…”
Section: Discussionmentioning
confidence: 88%
“…52 Abnormal expression of RB1 based on immunohistochemistry has been reported in few cases of thymoma. 53 In one case of type B3 thymoma, a high-level amplification was detected involving chromosomal band 8p12. This chromosomal region harbors a potential oncogene, namely the fibroblast growth factor receptor I, which has been reported to be amplified in other epithelial neoplasms, eg, in breast cancer and ovarian cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Few of the factors involved in regulating cell cycle control have been investigated in thymomas; even fewer studies have examined multiple factors in the same tumor series (7,8). The aim of this study was therefore to evaluate the expression of p53, p21, and p27 proteins in a homogeneous series of samestage thymomas to assess the integrity of cell cycle checkpoints in these tumors, to evaluate the coexpression of these proteins, and, finally, to examine the relationship between these cell cycle regulators and the clinicopathologic features of thymomas, including their ability to predict recurrence, and therefore necessity, of more accurate follow-up and supplemental therapy.…”
mentioning
confidence: 99%